GAMBARAN FAKTOR RISIKO TERJADINYA PERDARAHAN PASCA PERSALINAN DI RS NUR HIDAYAH BANTUL - Pratiwi, Fika (Jurnal Ilmu Kesehatan Mulia Madani Yogyakarta, 2025)
result in severe morbidity and even death for the mother. In addition, to prompt and appropriate treatment, it is also necessary to prevent and evaluate patients with risk factors for hemorrhage postpartum so that they can be prevented and maternal death does not occur. Objective: To find out the description of risk factors for hemorrhage postpartum at Nur Hidayah Hospital, Bantul in 2022. Research Methods: This type of research is to use a quantitative descriptive research method with secondary data collection obtained from original sources, namely medical records. The research location is Nur Hidayah Hospital, Bantul. The sampling technique is a total sampling of 60 mothers giving birth. Data analysis techniques by way of describing or describing the data that has been collected as it is. Results: The results showed that the risk factors for postpartum hemorrhage based on age were not at risk of 40 people (66.7%) who were at risk of 20 people (33.3%), based on parity not at risk of 43 people (71.7%) who were at risk of 17 people (28.3%), based on the distance between pregnancies and births not at risk 50 people (83.3%) who are at risk 10 people (16.7%), based on prolonged parturition who are at risk 40 people (66.7%) are not at risk 20 people (33.3%) and based on anemia who were not at risk as many as 34 people (56.7%) and at risk (43.3%). Keywords: Hemorrhage Postpartum, Risk Factor